JENIS DAN BENTUK METAFORA DALAM KISDAP “JULAK AHIM” KARYA JAMAL T. SURYANATA - Siti Jamzaroh (Balai Bahasa Kalimatan Selatan, 2018)
This research is aimed to find out 1) to know the type of metaphor of Kisdap